Developing Communicative Competence in Future Translators through Interdisciplinary Approaches (Ta'limning zamonaviy transformatsiyasi, 2024)
In an era characterized by the relentless evolution of global communication, the demand for highly skilled translators has reached unprecedented heights. This article delves into the innovative realm of developing communicative competence in future translators through the integration of interdisciplinary approaches. Traditional translation training methods are scrutinized, and a transformative methodology is proposed. By weaving together insights from linguistics, cultural studies, technology, and business, this approach aims to create a comprehensive training program. The article systematically explores curriculum redesign, technology integration, and faculty development, contributing to the advancement of translator education and the evolution of the translation profession.